Study of the influence of temperature and water level of the reservoir about the displacement of a concrete dam - Oro, Sheila; Mafioleti, Tereza; Chaves Neto, Anselmo; Garcia, Suellen Ribeiro Pardo; Neumann Júnior, C. (Zielona Góra: Uniwersytet Zielonogórski)
Multivariate techniques are used in this study to analyze the monitoring data displacements of a concrete dam, measured by means of pendulums, extensometer bases and multiple rod extensometers, taking into account the action of environmental conditions, bounded by the surface temperature of the concrete at ambient temperature and the tank water level. The canonical correlation analysis is used to evaluate the influence of environmental variables in the displacement of structures and dam foundations.
Keywords: structural monitoring; concrete dam; multivariate analysis